Pastorale begeleiding van die emosioneel verwonde tiener - W. Coetzer; T. C. de Klerk (Acta Theologica)
Many teenagers struggle with the consequences of emotional injuries. Simultaneously they are moving through the difficult phase of adolescence which may complicate their situation. In this article the first focus is the typical factors which compound the difficulties in this phase. Secondly we focus on a variety of possible causes of emotional injury. The results and consequences of such injuries form the third issue investigated. In the last instance attention is given to some pastoral-theological points of departure concerning counselling of emotionally injured young people. To these young people their frame of reference is influenced by amongst other things their families, school, church and friends. To experience real meaning in life the teenager’s relationship with God has to be healed, for this relationship determines all other inter-personal relationships. The spiritual deepening accompanying this process often also significantly contributes to the eventual handling of unprocessed hurt from the past.